Glass‐Ceramic Composites from Borosilicate Glass and Alumina‐Rich Residues. (20th November 2013) - Chinnam, Rama Krishna; Boccaccini, Aldo R.; Bernardo, Enrico; Epstein, Howard
Abstract : Valoxy, an alumina‐rich waste, was mixed with borosilicate glass (BSG) powder in 10, 20, and 30 wt% concentrations. Sintering was carried out at 850 and 950°C for 30 min. Glass‐ceramics (GC) were characterized by X‐ray diffraction analysis and scanning electron microscopy. Diametral compression strength (DCS) tests were performed on sintered samples before and after thermal shock. GC samples containing calcined Valoxy showed superior properties in all compositions and processing temperatures compared with samples containing as‐received Valoxy. Maximum density of 2.2 g/cm 3, water absorption below 1 wt% and DCS of ~24MPa were measured for 10 wt% calcined Valoxy + BSG GC composites sintered at 850°C.